In vivo targets of human placental micro-vesicles vary with exposure time and pregnancy. Issue 6 (June 2017) - Tong, Mancy; Chen, Qi; James, Joanna L; Wise, Michelle R; Stone, Peter R; Chamley, Lawrence W
Abstract : Throughout human gestation, the placenta extrudes vast quantities of extracellular vesicles (EVs) of different sizes into the maternal circulation. Although multinucleated macro-vesicles are known to become trapped in the maternal lungs and do not enter the peripheral circulation, the maternal organs and cells that smaller placental micro-vesicles interact with in vivo remain unknown. This study aimed to characterise the interaction between placental micro-vesicles and endothelial cells in vitro and to elucidate which organs placental micro-vesicles localise to in vivo . Placental macro- and micro-vesicles were isolated from cultured human first trimester placental explants by sequential centrifugation and exposed to human microvascular endothelial cells for up to 72 h. In vivo, placental macro- and micro-vesicles were administered to both non-pregnant and pregnant CD1 mice, and after two or 30 min or 24 h, organs were imaged on an IVIS Kinetic Imager. Placental EVs rapidly interacted with endothelial cells via phagocytic and clathrin-mediated endocytic processes in vitro, with over 60% of maximal interaction being achieved by 30 min of exposure. In vivo, placental macro-vesicles were localised exclusively to the lungs regardless of time of exposure, whereas micro-vesicles were localised to the lungs, liver and kidneys, with different distribution patterns depending on the length of exposure and whether the mouse was pregnant or not. The fact that placental EVs can rapidly interact with endothelial cells and localise to different organs in vivo supports that different size fractions of placental EVs are likely to have different downstream effects on foeto–maternal communication.